Between Constitutional Mandate and Asset Accumulation: Governance Failure Typologies in Indonesia’s Land Bank Agency - Widyarini Indriasti Wardani; Sigit Irianto; Markus Suryo Utomo; Zainal Amin Ayub (Faculty of Sharia, Universitas Islam Negeri (UIN) Profesor Kiai Haji Saifuddin Zuhri Purwokerto, Indonesia, 2026)
Land inequality in Indonesia reveals a persistent tension between Article 33(3) of the 1945 Constitution and state land management practices that increasingly rely on institutional asset accumulation. Existing studies on land banking and land governance have examined institutional reliability, redistribution potential, and centralised administration, but have not sufficiently explained how the legal architecture of Indonesia’s Land Bank Agency may structurally generate governance failures. This study evaluates whether the Land Bank Agency, established under Government Regulation Number 64 of 2021, enables constitutional land redistribution or reinforces asset accumulation. Applying a socio-legal research design, the study links normative-doctrinal analysis with document review and field evidence from Semarang City, Kendal Regency, and Batang Regency. Data were collected through semi-structured interviews using open-ended questions with local ATR/BPN officials and were triangulated with spatial planning documents, land administration materials, secondary socio-economic data, and critical academic literature to reduce institutional bias. Using the Constitutionally-Embedded Land Governance (CELG) framework, this study identifies four governance failure typologies: centralisation bias, asset idleness failure, coordination failure, and regulatory fragmentation failure. The findings show that these failures are rooted in centralised legal design rather than mere implementation defects. The study proposes Constitutional Land Banking (CLB) to reorient land banking toward decentralised authority, compensation guarantees, mandatory FPIC, and inter-regime coordination.